PENGARUH MODAL SENDIRI DAN MODAL PINJAMAN TERHADAP SISA HASIL USAHA (SHU) KOPERASI KOTA SUKABUMI - Rohmansyah, Tria; Sudarijati, Sudarijati (Fakultas Ekonomi Universitas Djuanda, 2017)
This research purpose how the influence of their own capital and loan capital of net income cooperative in Sukabumi City. This research is quantitative descriptive study using multiple regression analysis. The sampling technique used was purposive sampling where the sampling is based on certain criteria. From the established criteria, obtained 11 (eleven) sample cooperative in sukabumi city with the observation period of 2 (two) years for each sample cooperative. The research analysis tools using multiple regression analysis. Simultaneous hypothesis testing using the F and partial test using t-test with a probability level of 5 percent (0,05). F-test result explain that the own capital and loan capital Simultaneous have a positive and significant effect on net income cooperative. t-test results showed that the own capital have a positive and significant effect on net income. While loan capital is not have significant impact on net income cooperative in Sukabumi City.Key words : Equity, Loan Capital, Net Profit Margin